Eestimaalaste moraalsete ja eetiliste hoiakute muutumine 1995–2020 - Remmel, Meego; Lilleoja, Laur (Usuteaduslik Ajakiri, 2025)
The change in the moral and ethical attitudes of Estonians from 1995 to 2020 This analysis highlights significant shifts in the moral and ethical attitudes of Estonians over the past 25 years, reflecting broader societal transformations. In the 1990s and early 2000s, there was a tendency towards conservatism, but this trend has shifted markedly towards liberalism in recent years. The last decade, in particular, has seen a notable increase in tolerance towards issues such as extramarital relationships, homosexuality, abortion, and euthanasia. These changes are consistent with broader European and North American trends. A clear distinction exists between the moral and ethical views of ethnic Estonians and other language groups in Estonia, with Estonians tending to be more liberal. This difference is likely influenced by the general information environment rather than ethnic characteristics, suggesting that people’s attitudes are shaped more by the media and societal influences than by cultural or linguistic factors. Religious affiliation and community involvement also play a crucial role in shaping moral and ethical views. Those who are actively engaged in religious communities, particularly in free church or Catholic contexts, tend to hold more traditional values. This is in contrast to those with weaker ties to religious institutions, who are more susceptible to secular influences. The findings support previous research showing that active participation in religious life strengthens specific moral convictions and virtues. In contrast, weakened or severed ties to religious communities lead to a drift away from religious practices and values, resulting in a more secular and less morally defined identity.